Developmental Venous Anomaly Complicated by Cerebral Venous Infarction - Parker, Brian J. (Radiol Case Rep, 2015)
Developmental venous anomaly is a vascular malformation thought to be a benign embryologic variant. We describe a patient who presented with focal neurological deficits and parathesia due to an infarct associated with a developmental venous anomaly with a thrombosed draining vein.